Nivel de contaminación enteroparasitaria de lechugas (Lactuca Sativa) irrigadas con aguas del Río Rímac para consumo humano en la zona de Carapongo. - Palacios Morales, Félix Nicolás (2019)
Objective: This study aimed to determine the enteroparasitosis pollution level from lettuce meant for human consumption irrigated with wastewater from the Rimac River in post-harvest season. Methodology: It were establishedthree study sites: Z-1 Cuncacucho hill curve; Z-2 the bridge area or the Carapongo market, 50 meters from the riverbank; and Z-3 around the bus stop The Portillo 50 meters away from the river bank. The lettuce samples (Lactucasativa) were taken in situ in the number of two lettuce heads from which it was used approximately 200 grams of basal leaves which were in direct contact with the soil and water during the irrigation period. The collection was donethrough the use of examination gloves, scalpels, simple tweezers and the samples were collected in polyethylenecrystal bags with security locks. The samples were processed by the direct method of observation and by the modified Ziehl Neelsen coloring technique. Results: The results showed that there were enteroparasitosis contaminationlevels in the lettuce leaves with the following parasites: blastocystis hominis (23.88%), balantidium coli (4.47%),entamoeba coli (1%), Cryptosporidium spp. (10.44%), Giardia lamblia. (8.95%), Ascaris lumbricoides (17.91%),Entamoeba hystolitica (19.40%), Isospora sp (2.98%), Toxocara sp (5.97%). Given these results, it is necessary totake control measures to improve the hygienic health quality for these foods. From the results found in this study it is recommended a continuous monitoring in the lettuce post-harvest procedure for being a horticultural product fordirect consumption. Conclusions: It was found the presence of species of enteroparasites in lettuce (Lactuca sativa)for human consumption irrigated with sewage water that comes from Rimac River in the Carapongo horticulturearea. The highest percentage of enteroparasites were Blastocystis hominis 29.91%, Entamoeba hystolitica 19.03%,Ascaris lumbricoides 17.84%, Cryptosporidium s 11.14% respectively. It was possible to assess the presence ofenteroparasites in various levels described as high, medium, regular and low by the WHO standards.